Synthesis of some derivatives of n-(2,3,4,6-tetra-o-acetyl-õ-d-glucopyranosyl)-n’-(benzothiazole-2’-yl) thioureas - Thanh, Nguyen Dinh; Lan, Pham Hong; Huyen, Nguyen Thu (Vietnam Journal of Chemistry, 2014)
Some compounds of N-(2,3,4,6-tetra-O-acetyl-β-D-glucopyranosyl)-N’-(benzothiazole-2’-yl)thioureas have been synthesized from corresponding 2,3,4,6-tetra-O-acetyl-β-D-glucopyranosyl isothiocyanate and the substituted derivatives of 2-aminobenzothiazoles executing in home microwave oven. Their spectroscopic properties have been recorded and the relationships between their structures and spectral properties (IR, 1H- and 13C-NMR) have been discussed